Multiscale-Band K-Distribution Model for Molecules in High-Temperature Gases - Shi, Lei; Zhang, Yuyue; Li, Fangyan; Du, Yuefan; Yao, Bo (Journal of Spectroscopy, 2022)
Radiation heat transfer plays a dominant role in high-temperature flow field. Rapid and reliable calculation of spectral radiation properties is beneficial for thermal analysis and detection of radiation target. In this paper, a multiscale-band k-distribution model is proposed for the study of radiation properties in high-temperature gases. The accurate absorption coefficients are firstly calculated using the line-by-line model. The slope of the accurate absorption coefficient line and its slope threshold are then extracted and analyzed, which act as a basis to divide the absorption coefficient line into multiple segments. For different segments, different bandwidths are chosen for the corresponding band k-distribution model. In the model, the 7-point Gauss–Lobatto method is employed to obtain the optimized absorption coefficients. These optimized absorption coefficients formed the absorption coefficient database. The radiation intensities of gases are finally calculated and analyzed based on the optimized database. Experimental results suggest that the multiscale-band k-distribution model can improve the efficiency up to 35% compared with the widely used narrow-band k-distribution model. Simultaneously, the relative calculation error is less than 5% compared with the most accurate line-by-line model.